Overtraining and detection of overtraining by heart rate monitors - Rusko, H. (2000)
Overtraining is a process of excessive training and insufficient recovery that may lead to overtraining syndrome: persistent fatigue, performance decrease, neuroendocrine and immunological changes, alterations in mood states etc. The mechanisms underlying overtraining and overtraining syndrome seems to be related to physical and psychological stress of training and stress theory can be applied to study overtraining. Two types of overtraining syndrome have been described in the literature, sympathetic and parasympathetic type, and they are supposed to represent different stages of the stress response. Cardiovascular autonomic function tests based on heart rate (HR) and HR-variability (HRV) measurements have been developed to study the sympathetic and parasympathetic activation. Sympathetic activation increases and parasympathetic activation decreases supine (HRsup) and standing (HRstand) heart rate. During standing up the acute increase in heart rate is mainly parasympathically controlled. In addition, parasympathetic activation increases HRV. In 1980's, we have used Polar HR-monitors (5-s recording interval) to measure HRsup and HRstand variables in several longitudinal studies on Finnish elite athletes. These studies have shown that experimental overtraining leads to increased HRsup and HRstand and that the changes in HRstand are related to the changes in performance. Altitude training studies have also shown that HRsup and HRstand reflect the changes in stress due to hypoxia. In 1990's, Polar HR-monitors have allowed beat-by-beat recording of RR-intervals and the use of time and frequency domain analysis of HRV. HRV has been found to increase with the increase in VO2max while overtraining has decreased HRV. Because no single measure of HR or HRV has been able to unambiguously indicate overtraining an overtraining index including several supine and standing HR- and HRV-variability measures in the orthostatic test was developed and found to indicate the changes in physical and psychological stress. (2000 Pre-Olympic Congress, Sports Medicine and Physical Education, International Congress on Sport Science, 7-13 September - Brisbane, Australia 2000)